The extent to which review for unreasonableness is meaningfully incorporated in the promotion of Administrative Justice Act no. 3 of 2000 - Bednar, Jeannine (Rhodes University, Faculty of Law, Law, 2006)
Prior to the current constitutional dispensation, the development of South African administrative law was restricted by the doctrine of Parliamentary Sovereignty. Even in that comparatively 'hostile' environment, review for unreasonableness developed as an aspect of judicial review, and was applied as a check on the exercise of administrative power in certain circumstances. The principle of proportionality as an aspect of review for unreasonableness also developed during this period. With the advent of the new Constitutional dispensation, the framework within which administrative law in South Africa operates became one governed by Constitutional Supremacy. The Rights to Just Administrative Action, including a right to reasonable administrative action, were entrenched in the Constitution. Review for unreasonableness is an important aspect of administrative law in the present Constitutional dispensation as the mechanism for protecting the Constitutional right to reasonable administrative action. Proportionality is an important principle underlying the Bill of Rights as a whole, and it is an important aspect of the right to reasonable administrative action, and of review for unreasonableness. In early 2000, the Promotion of Administrative Justice Act No. 3 of 2000 ("the PAJA"), was passed by Parliament in fulfillment of the Constitutional requirement to pass legislation to give effect to the constitutional rights to Just Administrative Action. This thesis examines whether or not review for unreasonableness, and proportionality as an aspect of review for unreasonableness, have been meaningfully incorporated in the PAJA, and if they have not been, what potential remedies there might be. This is done by examining the basis of judicial review both before and under the current constitutional dispensation; defining unreasonableness, and proportionality; examining the content of the right to administrative action which is "justifiable in relation to the reasons given" in section 24(d) of the Interim Constitution and the right to reasonable administrative action in terms of section 33(1) of the Final Constitution; examining the application of review for unreasonableness and proportionality by the Courts both before and under the current constitutional dispensation; examining the content of judicial review incorporated in the PAJA and the drafting history of section 6(2) of the PAJA which relates to review for unreasonableness; drawing conclusions regarding whether or not review for unreasonableness and proportionality were meaningfully incorporated in the PAJA; and finally making recommendations with regard to review for unreasonableness and proportionality in light of the provisions of the PAJA.
Keywords: Administrative la; Administrative law -- South Africa; Judicial review of administrative acts -- South Africa; Law reform -- South Africa